ANALISIS KEBUTUHAN BAHAN AJAR DAN ASESMEN PEMBELAJARAN YANG MELATIHKAN KEMAMPUAN METAKOGNISI SISWA DALAM PEMECAHAN MASALAH KIMIA SMA KELAS XI SEMESTER I - Syahmani, Syahmani; Irhasyuarna, Yudha; Kusasi, M. (Vidya Karya Jurnal Kependidikan, 2013)
The objective of this research is to need analyze in learning chemistry, which will be used in developing teaching material and assessment of metacognitive in chemistry problems. This research is first step in Research and Development (Research and Development). The population involved all the Senior High Schools Students on Banjarmasin conducting Curriculum 2013. The samples were determined by purposive sampling, considering the acreditation status of each school. The samples are 4 schools (n = 272 students andÂ  n = 12 teachers) were enrolled in Banjarmasin Grade 11 chemistry classes. The data were collected by instrument test, check list, observation guide, interview guide and questionnaire; and analyzed by descriptive. The result showed that: (1) Average students academic achievement is under 60% and Their metacognitive abilities are still developing catagories (2) The schools management is fully supported for teaching and learning chemistry, but limited in inadequacy equipments and chemicals, and low of skills of laboratory assistant, (3) the teachers experience some obstacles for teching and learning chemistry, i.e. limitation of laboratory room and its facilities, inadequacy equipments and chemicals, and the teachers psychological factor which was unsatisfied that learning process without fully information,Â  (4) The students and teachers need teaching material and assessment of metacognitive.